1992
DOI: 10.1042/bj2880241
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of platelet-activating-factor receptors and the desensitization response in polymorphonuclear neutrophils

Abstract: Platelet-activating factor (PAF) desensitizes as well as stimulates its various target cells, We find that human polymorphonuclear neutrophils (PMN) exposed to PAF became maximally unresponsive to a second PAF challenge within 15-90 s in assays of Ca2+ mobilization and degranulation. The cells regained full PAF-sensitivity over the ensuing 20-40 min. These effects correlated with changes in PAF receptor availability. PMN treated with PAF, washed in regular buffer and assayed for PAF binding exhibited falls (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 39 publications
4
5
0
Order By: Relevance
“…Our finding that phorbol ester down-regulates PAFR is in agreement with several previous observations from human monocytes (23), neutrophils (29), and human neurohybrid cell lines (48,49). Nguer et al (11) reported that PMA increased PAFR mRNA and surface expression in human tonsillar B cells.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our finding that phorbol ester down-regulates PAFR is in agreement with several previous observations from human monocytes (23), neutrophils (29), and human neurohybrid cell lines (48,49). Nguer et al (11) reported that PMA increased PAFR mRNA and surface expression in human tonsillar B cells.…”
Section: Discussionsupporting
confidence: 83%
“…The combination of calcium ionophore and phorbol ester strongly activates B cells, and both agents have been reported to modulate the PAFR (23,28,29). In the present study, we found that both PDB and ION caused down-regulation of PAF binding sites on LA350 cells.…”
Section: Pdb and Ion Down-regulate Pafr On La350 Cellssupporting
confidence: 68%
See 1 more Smart Citation
“…Shirasaki et al [22] showed that PAF rapidly doubled its receptor mRNA in human monocytes, whereas others showed that PAF markedly reduced its receptor mRNA in U937 cells [23], in keeping with earlier studies in PMNs [24] and Kupffer cells [25], which demonstrated that PAF caused a down-regulation of cell surface PAF-binding sites. Quantitative study of tissue PAF-R mRNA, especially of its change over time during inflammation, has so far been limited.…”
Section: Introductionsupporting
confidence: 59%
“…Few studies investigating tissue PAF-Rs in i o have been reported, and only relative amounts of PAF-R mRNA have been assessed [21]. Previous studies in itro have demonstrated various effects of PAF on PAF-R binding and PAF-R gene transcription, but the results have been contradictory [22][23][24][25], and may be irrelevant to inflammation in i o. Using a highly sensitive Q-PCR method to quantify accurately PAF-R transcripts, we report here high expression of PAF-R in the small intestine, especially the ileum, during both normal and inflamed states.…”
Section: Discussionmentioning
confidence: 99%